2022
DOI: 10.1039/d1qm01573g
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic bistable organic ionic plastic crystal with room temperature ion conductivity comparable to NASICON and superionic conduction in a broad temperature window

Abstract: Organic ion plastic crystals (OIPCs) show promising applications in various all- solid-state electrochemical energy storage devices. In this regard, superionic conducting OIPCs with broad temperature window are highly demanded. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…As mentioned in DSC analysis, 1 displays the largest ratio of state numbers in 1-5, which is more than 4 times higher than that of 2-5, suggesting that the cations of 1 in the HT phase acquired much more rotational degrees of freedom and are easy to diffuse and migrate, and this superionic conduction mechanism is similar to the well-known one in organic ionic plastic crystals. [49][50][51]…”
Section: Impedances and Conductionmentioning
confidence: 99%
“…As mentioned in DSC analysis, 1 displays the largest ratio of state numbers in 1-5, which is more than 4 times higher than that of 2-5, suggesting that the cations of 1 in the HT phase acquired much more rotational degrees of freedom and are easy to diffuse and migrate, and this superionic conduction mechanism is similar to the well-known one in organic ionic plastic crystals. [49][50][51]…”
Section: Impedances and Conductionmentioning
confidence: 99%
“…Especially, some [M(mnt)] − complexes with Λ-shaped benzylpyridine cations and other cations exhibit spin-Peierls-type magnetic transition with structural phase change behavior due to magnetic–lattice interaction. 28–33 For these metal–bis-dithiolene complexes, halogen substitution on the counter ions is also an effective way to change the arrangement of [M(mnt)] − and [M(dmit)] − anions and to improve the magnetic properties within metal–bis-dithiolene spin systems. 34–39 Ren et al reported a series of research works on 1D spin-Peierls-like complexes assembled from [Ni(mnt) 2 ] − with shaped 1-(4′-X-benzyl)pyridimium derivatives (X represents a halogen substituent).…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have identified ionic plastic crystals (IPCs) as promising candidates for the development of novel solid-state electrolytes or as dopants to be incorporated within Nafion-based membranes. As electrolyte materials, they offer several advantages such as non-inflammability, low vapor pressure, plasticity, higher thermal stability, and of course, intrinsic ionic conductivity favored by their intrinsic dynamic nature. , …”
Section: Introductionmentioning
confidence: 99%